2019
DOI: 10.3390/ijerph16173184
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival Microbiota of Mexicans with Type 2 Diabetes with Different Periodontal and Metabolic Conditions

Abstract: Background: Type-2-Diabetes (T2D) and Periodontitis are major inflammatory diseases. However, not much is known about the specific subgingival microbiota in Mexicans with diabetes and metabolic dysbiosis. The aim of this study was to describe the subgingival microbiota of Mexicans with T2D and the different periodontal and metabolic conditions, through “Checkerboard” DNA–DNA hybridization. Methods: Subjects were divided into two groups—periodontal-health (PH) (PH_non-T2D; n = 59, PH_T2D; n = 14) and generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…forsythia ). 203 , 204 On the other hand, Rodriguez‐Hernandez et al 205 found a decrease in red complex bacteria in Mexican individuals with type 2 diabetes compared with normoglycemic individuals with periodontitis. However, individuals with type 2 diabetes and periodontitis had higher levels of the yellow and orange complexes.…”
Section: Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…forsythia ). 203 , 204 On the other hand, Rodriguez‐Hernandez et al 205 found a decrease in red complex bacteria in Mexican individuals with type 2 diabetes compared with normoglycemic individuals with periodontitis. However, individuals with type 2 diabetes and periodontitis had higher levels of the yellow and orange complexes.…”
Section: Diabetesmentioning
confidence: 99%
“…However, individuals with type 2 diabetes and periodontitis had higher levels of the yellow and orange complexes. 205 There are also some contradictions among different studies when analyzing individual bacterial species. For instance, Po.…”
Section: Diabetes Affecting the Subgingival Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Before the extensive use of high-throughput sequencing, culture-based methods and DNA-DNA hybridization checkerboard-based techniques were widely used and already affirmed the predominance of Capnocytophaga spp. in gingivitis (Testa, 2016), diabetes (Rodriguez-Hernandez et al, 2019), and cancer (Jolivet-Gougeon et al, 2005, Jolivet-Gougeon et al, 2008 Accepted Article Hu et al, 2013a, Hu et al, 2013b. This bibliographic study has shown the role of Capnocytophaga spp.…”
Section: Discussionmentioning
confidence: 91%
“…A Mexican study found, unlike our results, that TIID subjects with generalized periodontitis had a lower percentage of the red complex than non-TIID subjects. 40 A British survey showed no impact of diabetes on the prevalence of Aa and Pg. 29 In addition to a Chinese report, according to our results, Tf are considered to be periodontitis-related bacteria.…”
Section: Discussionmentioning
confidence: 99%